DIRECT EFFECTS OF GM-CSF ON THE FUNCTIONS OF HUMAN MONOCYTES/MACROPHAGES - Natalia Dinislamovna Gasatova; Maksim Evgenievich Meniailo; Vladimir Vladimirovich Malashchenko; Andrei Gennadievich Goncharov; Olga Borisovna Melashchenko; Ekaterina Michailovna Morosova; Seledtsov Victor Ivanovich (Медицинская иммунология, 2019)
We investigated direct effects of granulocyte-macrophage colony-stimulating factor (GM-CSF) on the surface properties and cytokine-producing activity of human monocytes / macrophages (Mc/Mphs). The CD14+ cells were isolated from peripheral blood of healthy donors by positive magnetic separation. The isolated Mc/Mphs were cultured with lipopolysaccharide (LPS, 1 μg/ml) or without LPS for 24 hours. Membrane expression of CD14, CD16, CD119, CD124, and CD197 molecules was assessed by flow cytometry. The contents of tumor necrosis factor-α (TNF-α), interleukin-1β (interleukin-1β, IL-1β), IL-6 and IL-10 in culture supernatants were determined by the enzyme immunoassay technique. It was found that GM-CSF at a concentration range of 0.01-10 ng/ml did significantly reduce the number of cells expressing CD197 (CC receptor of chemokine 7), without significantly affecting the percentage of CD14+ (coreceptor of LPS), CD16+ (low-affinity Fc receptor), CD119+ (IFN-γ receptor) and CD124+ (IL4 receptor) cells. At the same time, GM-CSF reduced the contents of CD197+ macrophages, as well as CD14+, CD16 +, and CD119+ cells among the activated cell population, without significantly altering the number of CD124+ cells. It was also shown that GM-CSF (10 ng/ml), was able to enhance production of TNF-α and IL-6, but not IL-1β and IL-10 by activated Mc/Mphs. The results obtained indicate the ability of GM-CSF to exert both anti-inflammatory and pro-inflammatory effects upon macrophage cell populations. In general, such effects could contribute to the development of adaptive immunogenesis in peripheral tissues.